The Role of the Manager of the Qur'an House ‘Aisyah Radhiyallahu‘ Anha in Applying the Living Qur’an Method in Bangun Sari Village, Tanjung Morawa District, Deli Serdang Regency North Sumatra - Sinaga, Ali Imran; Ananda, Rusydi; Putri, Hairani Ananda (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to determine the role of the manager in managing the Qur'an House ‘Aisyah Radhiyallahu‘Anha in applying the living Qur’an method. This research method uses qualitative research and the approach used is descriptive method, which is describing and analyzing the role of the manager of the Qur'an house ‘Aisyah Radiyallahu‘Anha in applying the living Qur’an method. The results in this study the role of the house manager of 'Aisyah Radiyallahu' Anha in implementing the living Qur'an method as a facilitator, facilitating all activities related to community interaction with the Qur'an. an. In the implementation of the House of the Qur'an, first do it by teaching memorization of the Qur'an. A'ishah Radiyallahu's Qur'an House Program Plan ‘Anha in managing the Koran House of students should be able to memorize the Qur'an from children and mothers 1-2 juz per year and for independent classes 2 juz per year. The process of managing the Qur'an house Rumah Aisyah Radhiyallahu ‘Anha in applying the Living Qur’an method. Learning begins at 08.30 West Indonesian Time in the opening filled with muroja'ah after about 15 minutes of opening, students go to their respective groups. There are 3 classes in its implementation, juz 30, juz 29 and there are also independent classes that memorize 2 juz per year. After entering into each group there are those who are summoned one by one and some who come forward facing their ustadzah for rote and muroja'ah deposits. Each meeting of students deposited a memorization of 10-15 verses for duration of 45 minutes.